Dinámicas históricas y simbólico-culturales asociadas al ritual del Inti Raymi, Comunidad “La Calera” (2010 – 2018) - Maigua, Sami A. (2019)
This research paper’s aim is to analyze the historical and symbolic-cultural dynamics associated with the ritual of Inti Raymi, community "La Calera" (2010 - 2018). The research that has been done is a part of the qualitative research paradigm, developing interviews, life history and evocative self-ethnography. This research paper is broken down into three chapters; the first chapter is to theoretically base the processes of historical transformation and cultural symbolism in indigenous communities. The second chapter identifies the historical and symbolic elements in the oral memory of the community of Calera associated with Inti Raymi. For this, interviews were carried out and seven residents of this community were selected, that is, informants by relevance, who obtained deep and enriching knowledge. The third chapter qualitatively analyzes the diachronic evolution of social dynamics with evocative self-ethnography, having a clear result on these changes found in this research. Finally, this theoretical contribution was concluded thanks to the knowledge of the taytas and mamas of the community for the incentive of people interested in these processes of transformation and valorization.